The interpopulation differences between nucleotide sequence polymorphisms in alleles of the STR-loci of human chromosomal DNA - Zemskova, E Yu; Timoshenko, T V; Leonov, S N; Ivanov, P L (Sudebno-meditsinskaia ekspertiza, 2016)
The objective of the present work was to study the phenomenon of nucleotide sequence polymorphism in alleles of the STR-loci of human chromosomal DNA and to estimate its interpopulation differences with a view to the search for the molecular-genetic markers to be used as an efficient tool for the determination of belonging of the subjects of interest to a given population. We undertook the comprehensive analysis of amplified DNA fragment sequence polymorphism (AFSP) and amplified DNA fragment length polymorphism (AFLP) with the use of the PLEX-ID-TM analytical mass-spectrometry platform (Abbott Molecular, USA). The interpopulation differences were estimated in terms of the presence or the absence of single nucleotide replacements (SNP) in the STR markers based on a few population samples. Some of the loci of interest were found to have allelic variants the occurrence of which was significantly different in individual samples. Such alleles are of importance for the further investigation since they can be regarded as potential ethno-geographical markers. Their application opens up the new promising prospects for the expert detection of the ethnic affiliation of individual subjects.